Zeitschnitt '96 : Aktuelle Kunst aus Österreich - Brüderlin, Markus; Lindmayr, Ulli; Thoman, Elisabeth & Klaus; Thompson, Jon (Innsbruck : Kunstraum, 1996)
Feldner, Gottfried ; Gander, Mario ; Odradek, Geschwister ; Gstrein, Günter ; Gundolf, Eudokia ; Gundolf, Walter ; Gyurko, Stefan ; Holzknecht, Andreas ; Oberdanner, Annelies ; Pobitzer, Klaus ; Rosenberger, Isa ; Stecher, Clemens
biografie
Zeitschnitt '96 : Aktuelle Kunst aus Österreich
Duits
boek
Keywords: Oostenrijk